Resistance of compressed elements with small eccentricity taking into account actual height of the compressed concrete zone - I. T. Mirsayapov; G. T. Apkhadze (Vestnik MGSU)
Introduction. The load-bearing capacity of normal sections of eccentrically compressed reinforced concrete structures at small eccentricities, according to current regulatory documents, is determined taking into account the linear approximation of the nonlinear dependence of stresses in tensile reinforcement on the height of the compressed zone. This approach is largely simplified and in some cases leads to an unreasonable overestimation of the bearing capacity of elements. The aim of the study is to obtain analytically the most universal and accurate dependence for determining the height of the compressed zone of concrete, the stresses in tensile reinforcement and, as a result, to clarify the value of the maximum bearing capacity of the normal section of eccentrically compressed elements during destruction of the compressed zone in concrete. Objectives of the research: analytical obtaining the dependence for the height of the compressed zone of concrete in the section in the limit state; comparison of the obtained load-bearing capacity, taking into account the obtained dependence, with the simplest dependence adopted in regulatory documents, as well as with the results of calculations using a nonlinear deformation model; determination of the degree of unreasonable overestimation of the bearing capacity of eccentrically compressed reinforced concrete structures with small eccentricities in current regulatory documents.Materials and methods. The main methods used in the modern theory of concrete and reinforced concrete strength were adopted.Results. The analytical expression for the height of the compressed zone is obtained based on the simplified three-linear diagram of the deformation of concrete under compression. Reasonable refinement of the height of the compressed zone makes it possible to achieve maximum convergence with the results of calculations using a nonlinear deformation model without the use of iterative approaches to solving the problem.Conclusions. The proposed dependencies make it possible to determine the actual stress-strain state in normal sections of eccentrically compressed reinforced concrete elements under the action of small eccentricities of application of the longitudinal compressive force in the limit state.